Development of a human factors hazard model for use in system safety analysis - Birch, Dustin Scott, author; Bradley, Thomas, advisor; Miller, Erika, committee member; Cale, James, committee member; Ozbek, Mehmet, committee member (Colorado State University. Libraries, 2021)
Traditional methods for Human Reliability Analysis (HRA) have been developed with specific applications or industries in mind. Additionally, these methods are often complicated, time consuming, costly to apply, and are not suitable for direct comparison amongst themselves. The proposed Human Factors Hazard Model (HFHM) utilizes the established and time-tested probabilistic analysis tools of Fault Tree Analysis (FTA) and Event Tree Analysis (ETA), and integrates them with a newly developed Human Error Probability (HEP) predictive tool. This new approach is developed around Performance Shaping Factors (PSFs) relevant to human behavior, as well as specific characteristics unique to a system architecture and its corresponding operational behavior. This updated approach is intended to standardize, simplify, and automate the approach to modeling the likelihood of a mishap due to a human-system interaction during a hazard event. The HFHM is exemplified and automated within a commercial software tool such that trade and sensitivity studies can be conducted and validated easily. The analysis results generated by the HFHM can be used as a standardized guide to SE analysts as a well as design engineers with regards to risk assessment, safety requirements, design options, and needed safety controls within the system architecture. Verification and evaluation of the HFHM indicate that it is an effective tool for HRA and system safety with results that accurately predict HEP values that can guide design efforts with respect to human factors. In addition to the development and automation of the HFHM, application within commonly used system safety Hazard Analysis Techniques (HATs) is established. Specific utilization of the HFHM within system or subsystem level FTA and Failure Mode and Effects Analysis (FMEA) is established such that human related hazards can more accurately be accounted for in system design safety analysis and lifecycle management. Lastly, integration of the HFHM within Model-Based System Engineering (MBSE) emphasizing an implementation into the System Modeling Language (SysML) is established using a combination of existing hazard analysis libraries and custom designed libraries within the Unified Modeling Language (UML). The FTA / ETA components of the hazard model are developed within SysML partially utilizing the RAAML (Risk Analysis and Assessment Modeling Language) currently under development by the Object Management Group (OMG), as well as a unique recursive analysis library. The SysML model successfully replicates the probabilistic calculation results of the HFHM as generated by the native analytical model. The SysML profiles developed to implement HFHM have application in integration of conventional system safety analysis as well as requirements engineering within lifecycle management.